The power of information on customers' social withdrawal and citizenship behavior in a crowded service environment. (5th September 2018) - Wei, Shuqin; Ang, Tyson; Anaza, Nwamaka A.
Abstract : Purpose: Crowding in service environments is a constant concern for many firms due to the negative consequences it has on consumers and companies alike. Yet, scant empirical research exists on firm-generated initiatives aimed at improving customer service experiences in crowded situations. The purpose of this paper is to investigate how information, a managerially actionable variable, influences social interactions (in the form of customer social withdrawal and citizenship behavior) and service experience. Design/methodology/approach: Two experimental studies were conducted using an extended service context. Findings: This research demonstrates that receiving information about crowds in advance results in heightened social withdrawal, which improves customer service experience. However, providing consumers with a platform to share crowding information increases customers' citizenship behavior toward service employees and other customers, which, in turn, improves customer service experience. Practical implications: For extended service encounters (e.g. air travel) where social interactions are inevitable, companies should encourage customers to share their real-time experiences with other customers in hopes of creating more positive social interactions (e.g. citizenship behavior) within the crowded environment. Originality/value: Existing investigations of crowding stem from an overemphasis on the physical and atmospheric aspects of the environment by treating crowds as a "fixture" in the servicescape, rather than as "active participants" involved in the crowding environment. While the mere presence of crowds alone has negative effects, this research takes it a step further by examining interactions among and between customers and service employees within the crowded service environment.